Desain dan Analisis Tegangan Alat Pengangkat Roket Kapasitas 10 Ton Menggunakan Metode Elemen Hingga - Lasinta Ari Nendra Wibawa (Jurnal Energi dan Teknologi Manufaktur, 2019)
This study examines the design and stress analysis of a 10 ton capacity rocket lifting device using the finite element method. The material used is Aluminum alloy 7075. Finite element analysis is done numerically by using Autodesk Inventor Professional 2017. software The simulation results show that the structure of the rocket lift has Von Mises stress, deformation, mass, and safety factors of 46.34 MPa, 0.7947 mm, 186.75 kg, and 3.13.